Clinical Profile of RT-PCR Positive Paediatric Patients with COVID 19: Overview from Chattogram, Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Coronavirus diseases 2019 (COVID-19) has become global pandemic. During the COVID-19 pandemics, caused by SARS-CoV-2, overall, children younger than 18 years are thought to account for only 1% to 2% of detected cases worldwide. COVID-19 has been found less frequent in children and studies on pediatric COVID-19 have also been less reported, especially from Bangladesh. To evaluate the clinical profile of RT-PCR- positive paediatric patients with COVID 19 in Chattogram region.Materials and methods: This cross-sectional study was conducted in OPD, Department of Paediatrics, Chittagong Medical Colllege Hospital (CMCH) Chattogram. All postCOVID paediatric patients reported as RT-PCR positive by Microbiology department of CMCH were enrolled in the study. The study was carried out from 1/8/21 to 31/01/22. According to inclusion/exclusion criteria 96 RT-PCR positive COVID-19 paediatric patients were taken as sample by convenient sampling for this study. The diagnosis of COVID 19 infection was confirmed by RTPCR report of nasopharyngeal or oro-pharyngeal swab. Patients, guardians were contacted over telephone to attend paediatric OPD of CMCH for clinical information & laboratory findings.  Results: Among them 96 children, 68.8% were in >5 years, 18.8% were in 1-5 years, and 12.4% were in the